Physiological influence of silica on germinating pollen as shown by Raman spectroscopy. Issue 4 (13th May 2016) - Joester, Maike; Seifert, Stephan; Emmerling, Franziska; Kneipp, Janina
Abstract : The process of silicification in plants and the biochemical effects of silica in plant tissues are largely unknown. To study the molecular changes occurring in growing cells that are exposed to higher than normal concentration of silicic acid, Raman spectra of germinating pollen grains of three species ( Pinus nigra, Picea omorika, and Camellia japonica ) were analyzed in a multivariate classification approach that takes into account the variation of biochemical composition due to species, plant tissue structure, and germination condition. The results of principal component analyses of the Raman spectra indicate differences in the utilization of stored lipids, a changed mobilization of storage carbohydrates in the pollen grain bodies, and altered composition and/or structure of cellulose of the developing pollen tube cell walls. These biochemical changes vary in the different species. Abstract : Pollen grains germinating with and without silica are examined using Raman microspectroscopy. A three‐step hierarchical scheme is used to discriminate spectra of silica‐treated pollen grains from controls, due to different use of stored lipids, altered mobilization and distribution of carbohydrates in the pollen coat and in the germinating pollen tube. In Camellia japonica pollen, silica may have a direct influence on the structure of primary cell walls.